SELISIH TARIF RUMAH SAKIT TERHADAP TARIF INA-CBG’s PADA PASIEN SECTIO CAESAREA DI RUMAH SAKIT DAERAH IDAMAN BANJARBARU TAHUN 2019 - Mochammad Maulidie Alfiannor Saputera; Ahmad Ahmad; Anna Khumaira Sari; Ayu Soraya (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Caesar's operating rate continues to increase in every country, the World Health Organization (WHO) recommends the ideal Caesarean Section Rate (CSR) for a country is around 10% to 15%. INA-CBG’s is a payment with a package system based on the patient’s illness. In implementing the INA-CBG’s system, problems often occur in the financing. The thing that often happens is hospital rates in the Caesarean Sectio exceed INA-CBG’s claims. The study aims to determine the difference between hospital rates with claims of INA-CBG’s in Idaman Hospital Banjarbaru. This study is an observational hospital study of direct medical costs, data retrieved retrospectively from the JKN participant claims data of patients with Sectio Caesarea in 2019 in Hospital Idaman Banjarbaru as many as 833 data samples using samples jenuh. Data calculation to find out the difference is done by subtracking hospital rates with INA-CBG’s rates. The result showed the difference between hospital rates and INA-CBG’s rates in Sectio Caesarea patients in Hospital Idaman Banjarbaru is a negative difference of Rp. 3.908.338.992 (n=833) and the difference between the average hospital rates and the average INA-CBG’s rates is Rp.4.691.884 per patient.